Space charge layer evolution at yttria-stabilized zirconia grain boundaries upon operation of solid oxide fuel cells. (15th September 2022) - Chen, Yun; Abernathy, Harry; Hackett, Gregory; Fan, Yueying; Lee, Shiwoo; Gerdes, Kirk; Song, Xueyan
Abstract: Long-lasting solid oxide fuel cells (SOFC) rely upon an intact ionically conducting network in both the electrolyte and electrode. Understanding the impact of the high-temperature electrochemical operations on the possible nanostructure evolutions of ionic conductors is indispensable for the development of durable SOFC. Here we present possibly the first experimental evidence of space charge layer evolution of grain boundaries (GBs) of ionic conducting yttria-stabilized zirconia (YSZ) in a Ni/YSZ composite anode of SOFCs. Cells with identical Ni/YSZ composite anodes are either thermally treated or electrochemically operated using either dry or humidified H2 fuel for up to 3, 349 h. When operating under humidified H2 fuel, a discrete core-shell structure is found to develop exclusively along the YSZ/YSZ GB planes. The core-shell structure is elliptically shaped elongated along the GB planes. The core has a lower mass with a Y-depleted ZrO2-x with a cubic structure. The shell has a constant thickness of ∼1 nm and is Y-enriched. The nucleation and growth mechanisms of the core-shell structure are proposed in terms of the space charge layer evolution at YSZ GBs. The effect of the humidity in the fuel, the cell operating temperatures, and the current density on the formation of the core-shell structure is investigated. Graphical abstract: Image, graphical abstract